2007
DOI: 10.1093/ndt/gfm740
|View full text |Cite
|
Sign up to set email alerts
|

Human mesenchymal stem cells inhibit antibody production induced in vitro by allostimulation

Abstract: Our findings suggest that third-party MSC are able to suppress allo-specific antibody production in vitro, and may therefore help overcome a positive cross-match in sensitized transplant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(113 citation statements)
references
References 25 publications
5
107
1
Order By: Relevance
“…Moreover, thirdparty BMSCs transplantation could prolong skin graft survival time by inhibiting T lymphocyte activation and proliferation [43] . Third-party MSCs were able to suppress allo-specific antibody production in vitro, and they might rescue patients with life-threatening GVHD in vivo [44] . Likewise, the donor haematopoietic stem cells had the capacity to reduce the risk of GVHD [45] .…”
Section: Necrosismentioning
confidence: 99%
“…Moreover, thirdparty BMSCs transplantation could prolong skin graft survival time by inhibiting T lymphocyte activation and proliferation [43] . Third-party MSCs were able to suppress allo-specific antibody production in vitro, and they might rescue patients with life-threatening GVHD in vivo [44] . Likewise, the donor haematopoietic stem cells had the capacity to reduce the risk of GVHD [45] .…”
Section: Necrosismentioning
confidence: 99%
“…Furthermore, not only MSCs affect dendritic cell recruitment, maturation, and function but also significantly reduce monocyte differentiation into the dendritic cell type [149][150][151][152][153]. Last but not least, MSCs alter the phenotype, proliferation, cytotoxic potential, and cytokine secretion of NK-cells [147,154,155] and decrease proliferation, differentiation, chemotactic properties of B-cells [156][157][158][159], acting over virtually all of the most important aspects of an immune response.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…However, the immunosuppressive activity of MSCs from various sources, and especially from bone marrow, on the T cells of both animals and humans, natural killer (NK) cells (Guo et al 2006 ;Spaggiari et al 2008 ) , and B cells (Comoli et al 2008 ) has been demonstrated. In studies aiming to explain the mechanisms of immunosuppressive activity of the MSCs, it has been declared that when the MSCs are co-cultured with T cells, dendritic cells (DCs), effector T cells, or NK cells, they change the cytokine secretion profi les of the related cells to encourage an antiinfl ammatory effect or a tolerant phenotype (Chang et al 2006 ) .…”
Section: Immunosuppressive and Immunomodulatory Properties Of Adult Smentioning
confidence: 99%